2015
DOI: 10.1177/0731948714566120
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Evidence-Based Literacy Practices in Middle School Response to Intervention

Abstract: The authors report findings from a systematic observational study of middle school educators (Grades 6–8) in two states who provided reading interventions within Tier 2 and Tier 3 of a Response to Intervention (RTI) framework. Intervention sessions were coded and analyzed to understand (a) the frequency and type of evidence-based strategies implemented for students with learning disabilities and reading difficulties, and (b) whether observed practices within secondary and tertiary intervention settings align w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…With specific attention towards the used research designs in the reviewed studies, the authors found that the most frequently used research design is quantitative design as there are 14 research articles chose to analyse their data using the quantitative methodological approach (see see AD-Heisat et al, 2009;Alsheikh & Mokhtari, 2011;Chen & Chen, 2015;De Leon & Tarrayo, 2014;Kasemsap & Lee, 2015;Lai, 2017;Melekoglu & Wilkerson 2013;Semtin & Maniam, 2015;Yukselir, 2014;Wai, et al, 2014;Teba, 2017;Semtin & Maniam, 2015;Migdadi & Baniabdelrahman,2016;and Nasab & Ghafournia, 2016). This is followed by seven studies that employed qualitative research designs (see Alsheikh & Mokhtari, 2011;Bastug & Demirtas, 2016;Ciullo, et al, 2016;De Leon & Tarrayo, 2014;Nurie, 2017;Omar & Saufi, 2015;Wai et al, 2014) and seven studies that employed mixed-method research designs (see Semtin & Maniam, 2015;Teba, 2017;Kasemsap & Lee, 2015;Li, 2010;Lai, 2017;Solak & Altay, 2014;Tercanlioglu, 2004). main tool to collect qualitative data (see Bastug & Demirtas, 2016;Nurie, 2017;Omar & Saufi, 2015;Semtin & Maniam, 2015;Teba, 2017;Wai et al, 2014;Tercanlioglu, 2004;Semtin & Maniam, 2015).…”
Section: Research Methodologies Used Research On Reading Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…With specific attention towards the used research designs in the reviewed studies, the authors found that the most frequently used research design is quantitative design as there are 14 research articles chose to analyse their data using the quantitative methodological approach (see see AD-Heisat et al, 2009;Alsheikh & Mokhtari, 2011;Chen & Chen, 2015;De Leon & Tarrayo, 2014;Kasemsap & Lee, 2015;Lai, 2017;Melekoglu & Wilkerson 2013;Semtin & Maniam, 2015;Yukselir, 2014;Wai, et al, 2014;Teba, 2017;Semtin & Maniam, 2015;Migdadi & Baniabdelrahman,2016;and Nasab & Ghafournia, 2016). This is followed by seven studies that employed qualitative research designs (see Alsheikh & Mokhtari, 2011;Bastug & Demirtas, 2016;Ciullo, et al, 2016;De Leon & Tarrayo, 2014;Nurie, 2017;Omar & Saufi, 2015;Wai et al, 2014) and seven studies that employed mixed-method research designs (see Semtin & Maniam, 2015;Teba, 2017;Kasemsap & Lee, 2015;Li, 2010;Lai, 2017;Solak & Altay, 2014;Tercanlioglu, 2004). main tool to collect qualitative data (see Bastug & Demirtas, 2016;Nurie, 2017;Omar & Saufi, 2015;Semtin & Maniam, 2015;Teba, 2017;Wai et al, 2014;Tercanlioglu, 2004;Semtin & Maniam, 2015).…”
Section: Research Methodologies Used Research On Reading Strategiesmentioning
confidence: 99%
“…main tool to collect qualitative data (see Bastug & Demirtas, 2016;Nurie, 2017;Omar & Saufi, 2015;Semtin & Maniam, 2015;Teba, 2017;Wai et al, 2014;Tercanlioglu, 2004;Semtin & Maniam, 2015). As for the observation data collection technique, there are five research studies used this technique to collect data (see Bastug & Demirtas, 2016;Ciullo et al, 2016;Omar & Saufi, 2015;Teba, 2017;Ulu, 2017).…”
Section: Research Methodologies Used Research On Reading Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A estos se añade, otros dos sobre documentos oficiales: "Me siento nervioso/a cuando tengo que hacer escritos oficiales: reclamaciones, formula-rios…" y otros cuatro generales del tipo: "Estudiar textos o construir textos son de las tareas que más temo". (Calderón, Parra y Piñeros, 2018;Connor et al, 2017;Ciullo et al, 2016;Guiñazú, Aldo y Zibelman, 2014;Li et al, 2018;OECD, 2016;Peng et al, 2019; (CEEDAR, 2019a;2019b;Ciullo et al, 2016;De la Paz et al, 2016;García et al, 2005;Graham et al, 2018;Karagiannopoulou, Milienos y Athanasopoulos, 2018;Li, Ye, Tang, Koster et al, 2015;Li et al, 2018;OCDE, 2016;Peng et al, 2019;Uttl, et al, 2017;Xie et al, 2018)…”
Section: Ansiedad Hacia El Aprendizaje Y La Evaluaciónunclassified